2017
DOI: 10.1007/s10047-017-0988-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with advanced heart failure and small body size undergoing continuous-flow left ventricular assist device implantation

Abstract: Left ventricular assist devices (LVADs) have become a preferred treatment option for patients with end-stage heart failure when used as a bridge to transplant or as a destination therapy. However, the association between small body size and postoperative outcomes for continuous-flow (CF) LVAD recipients is still being studied. We sought to determine whether body surface area (BSA) is associated with patient outcomes after CF-LVAD implantation. The study cohort of our single-center, retrospective review consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Smaller patients more often receive an HVAD, because of its smaller size. A retrospective study showed that a small BSA is an independent predictor for mortality after LVAD implantation 14 . Within the UMCU, HM3 is implanted since December 2015, whereas the first HVAD was implanted in November 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller patients more often receive an HVAD, because of its smaller size. A retrospective study showed that a small BSA is an independent predictor for mortality after LVAD implantation 14 . Within the UMCU, HM3 is implanted since December 2015, whereas the first HVAD was implanted in November 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study showed that a small BSA is an independent predictor for mortality after LVAD implantation. 14 Within the UMCU, HM3 is implanted since December 2015, whereas the first HVAD was implanted in November 2010. Because of the growing experience over the years, it is likely that treatment of complications continuously improves over the years.…”
Section: Discussionmentioning
confidence: 99%